2018
DOI: 10.22462/05.06.2018.11
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of hyperbaric oxygen therapy as a supplementary therapy of sudden sensorineural hearing loss in the Slovak Republic

Abstract: We evaluated the efficacy of hyperbaric oxygen (HBO2) therapy used as a supplement to the first-line medical treatment of sudden sensorineural hearing loss (SSNHL). We tested 68 patients suffering from SSNHL within seven days of hearing loss: 21 patients received the standard treatment protocol of our department (control group) and 47 individuals were treated with an additional application of HBO2 therapy. Treatment success was assessed using pre- and post-treatment audiograms. Outcomes of our study showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(41 citation statements)
references
References 0 publications
1
35
0
Order By: Relevance
“…In 2021, Tong et al showed in their RCT that 60.6% of patients in the HBOT + SS group achieved >15 dB hearing improvement compared with only 42.9% in the SS group 33 . Recently, combined therapy with SS, ITS, and HBOT has been introduced, and a systematic review of three prospective RCTs with 88 participants showed that the mean hearing gain (mean difference, 10.3 dB) and the odds ratio of hearing recovery (4.3) were higher with the triple combination therapy than with the control therapy 15–18 . Although triple combination therapy has been shown to be sufficiently effective, no standardized HBOT protocol has been established.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In 2021, Tong et al showed in their RCT that 60.6% of patients in the HBOT + SS group achieved >15 dB hearing improvement compared with only 42.9% in the SS group 33 . Recently, combined therapy with SS, ITS, and HBOT has been introduced, and a systematic review of three prospective RCTs with 88 participants showed that the mean hearing gain (mean difference, 10.3 dB) and the odds ratio of hearing recovery (4.3) were higher with the triple combination therapy than with the control therapy 15–18 . Although triple combination therapy has been shown to be sufficiently effective, no standardized HBOT protocol has been established.…”
Section: Discussionmentioning
confidence: 99%
“…33 Recently, combined therapy with SS, ITS, and HBOT has been introduced, and a systematic review of three prospective RCTs with 88 participants showed that the mean hearing gain (mean difference, 10.3 dB) and the odds ratio of hearing recovery (4.3) were higher with the triple combination therapy than with the control therapy. [15][16][17][18] Although triple combination therapy has been shown to be sufficiently effective, no standardized HBOT protocol has been established. Considering that HBOT is a costly and time-consuming intervention compared with corticosteroid treatment, it is imperative to identify a protocol that can produce the maximum effect in the shortest time and under minimum pressure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A major shortcoming was that most of its overall effects were predominantly driven by the over weighting of Khater et al, 4 an RCT with a total of only 22 participants, resulting in an unconvincing clinical conclusion. In a letter in reply, 5 the authors maintain the validity of their conclusion after excluding Khater et al 4 Their justification was given that the remaining 2 studies were also short of data consistency: the proportion of patients showing a hearing gain of 10 dB or greater was 81.7% (25 of 30 patients) in the control group of Cho et al 6 compared with 28.6% (6 of 21) in the control group of Krajčovičová et al 7 Naturally, this raises a second concern, that it could be challenging to examine the model assumptions if the number of studies is very small. Technically, the conventional I 2 statistic to test study heterogeneity for randomeffects modeling is biased in small meta-analyses.…”
mentioning
confidence: 99%